Does Literacy Affect Business Sustainability? Evidence from MSMEs - Rohyana Nur Isnaeny; Dewi Susilowati (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
After the Covid-19 event, most MSMEs faced problems that impacted the sustainability of MSMEs businesses. The problems faced by most MSMEs include a decrease in asset value. Based on resource-based theory, companies can utilize strategic assets in the form of both tangible and intangible assets so that companies can compete. This study aims to examine the effect of intangible assets in the form of examining the effect of financial and digital literacy on business sustainability. This research is a type of causal-comparative quantitative research. The sample in this study used convenient sampling and obtained a sample of 54 MSMEs. Multiple regression analysis is used to analyze research data. The authors collect data through a questionnaire with a Likert scale of 1 to 7. The results show that financial literacy has a positive effect on business sustainability and digital literacy has no effect on business sustainability. This research provides implications for MSMEs to be able to optimize intangible assets in company management.